A New Chalcone Derivative C49 Reverses Doxorubicin Resistance in MCF-7/DOX Cells by Inhibiting P-Glycoprotein Expression - Wang, Ting; Dong, Jingjing; Yuan, Xu; Wen, Haotian; Wu, Linguangjin; Liu, Jianwen; Sui, Hua; Deng, Wanli (Frontiers in Pharmacology, 2021)
Objective: C49 is a chalcone derivative. The aim of the current study is to illuminate the efficacy of C49 in reversing multidrug resistance (MDR) in MCF-7/DOX cells and its underlying molecular mechanism. Methods: The cytotoxic effects of C49 on MCF-7/DOX cells were evaluated by MTT assay using different concentration (0-250 μmol/l) of C49. Cell proliferation was evaluated by colony formation assay. Cell death was examined by morphological analysis using Hoechst 33258 staining. Flow cytometry and immunofluorescence were utilized to evaluate the intracellular accumulation of doxorubicin (DOX) and cell apoptosis. The differentially expressed genns between MCF-7 and MCF-7/DOX cells were analyzed by GEO database. The expression of PI3K/Akt pathway proteins were assessed by Western blot (WB). The activities of C49 combined with DOX was evaluated via xenograft tumor model in female BALB/c nude mice. Results: C49 inhibited the growth of MCF-7 cells (IC50 = 59.82 ± 2.10 μmol/l) and MCF-7/DOX cells (IC50 = 65.69 ± 8.11 μmol/l) with dosage-dependent and enhanced the cellular accumulation of DOX in MCF-7/DOX cells. The combination of C49 and DOX inhibited cell proliferation and promoted cell apoptosis. MCF-7/DOX cells regained drug sensibility with the combination treatment through inhibiting the expression of P-gp, p-PI3K and p-Akt proteins. Meanwhile, C49 significantly increased the anticancer efficacy of DOX in vivo. Conclusions: C49 combined with DOX restored DOX sensitivity in MCF-7/DOX cells through inhibiting P-gp protein.